Corpos hígidos: o limpo e o sujo na Paraíba (1912-1924) - Soares Junior, Azemar dos Santos (2011)
This work linked to the research line of Regional Hystory Graduate Program in History of the Federal University of Paraíba, with a major in History Culture aims to discuss the hygiene oh the body in the city of Parahyba. During the early twentieth century several media devices such as the newspapers A Imprensa and A União and the Era Nova magazine, were launched with the function of regulating the population of Paraiba from the new so-called civilizing precepts. Added to this documentation to the reports of Public Health and Hygiene Inspectorate under the guidance of doctors dictate standards of conduct, cleanliness and hygiene for the body mind and soul. The selected area was opened in 1912, the year the city Parahyba started to fear the ―terrible invasion‖ of bubonic plague that devastated the cold city of Campina Grande and ends in 1924, year that the Medical Society of Paraíba organized the Medical Week, a scientific event that had the objective of discussing eugenics and hygiene and its application in the city, in schools and in the body. The dissertation takes its inspiration from the body and the Historiography of the body and medicalization, developed mostly from the late twentieth century, due to the dialogue of history with other disciplines, like sociology, anthropology and medicine. Analyzing the cleanliness of the body in the city of Parahyba was walking through a world that reeked of sour, monuments of garbage and mud puddles, were created, for people who mixed with filth and realizing that this model that was once dirty little by little was replaced by the clean. Principles dictated by the teaching manuals of civility who wanted historical healthy bodies of clean and fragrant.